La Charte canadienne des droits et libertés et quelques leçons tirées de la Convention européenne des droits de l'homme - Tremblay, Guy (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
Many provisions of the Canadian Charter of Rights and Freedoms enacted as part of the Constitution Act, 1982 are couched in very broad terms. Comparative law provides useful guide-lines for ascertaining the probable ambit of the Charter. This article centers on the European Convention on Human Rights and on part of its case-law in areas where comparable solutions are likely to obtain in Canada. Thus, in spite of the generality of the words used by Deschênes J. in the case respecting minority language educational rights in Quebec, it is fair to assume that section 1 of the Canadian Charter will permit denials as well as limitations of rights, in exceptional circumstances, but that it will not apply to certain rights, such as the right not to be subjected to cruel treatment. More generally, the European Convention lays down the exhaustive limits that can apply to some rights and one may assume that no more restrictions would be permissible in Canada either. Finally, examples are given of cases which have been decided by the European Commission or the European Court of Human Rights and which pose problems likely to be raised under the Canadian Charter.